2018
DOI: 10.5380/reterm.v17i2.64129
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis of an Electric Vehicle Using Pamvec

Abstract: Electric vehicles are considered a key technology to reduce fossil fuel consumption, emissions and energy consumption. However, Electric Vehicles require larger battery packs to reach acceptable range levels. The development of new batteries with higher specific energy could reduce the mass and the cost of Electric Vehicles and increase their driving range. This work analyzes the influence of battery specific energy on battery pack mass, energy consumption and the cost per kilometer of a Tesla Model S Electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The equation for energy storage within vehicle inertia is given by, The above equation is a parametric expression for the average rate of energy storage, which is a consistent form of in equation (1). Therefore, the characteristic acceleration (ã) can be expressed as,…”
Section: Average Braking Lossesmentioning
confidence: 99%
See 1 more Smart Citation
“…The equation for energy storage within vehicle inertia is given by, The above equation is a parametric expression for the average rate of energy storage, which is a consistent form of in equation (1). Therefore, the characteristic acceleration (ã) can be expressed as,…”
Section: Average Braking Lossesmentioning
confidence: 99%
“…11, No. 4, December 2020 : 1987 -1994 1988 RERs and the constraints for the connection of electric vehicles (EVs) should be effectively addressed [1]. Energy storage could be one option to handle the uncertainty of RERs.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the manual and analytical work involved in the PHEV component sizing studies that can be found in the open literature is done by the designer. Simpson [11] and Termica [12] used the Parametric Analytical Model of Vehicle Energy Consumption (PAMVEC) model to analyze the component sizes. An automatic sizing procedure was created by Sharer et al, [13].…”
Section: Introductionmentioning
confidence: 99%

Power Requirement Study of Bus KITe PHEB in Kuala Terengganu

Wan Mohammad Aiman Wan Anuar,
Sathiis Kumar A/L Kanan,
Nurru Anida Ibrahim
et al. 2024
ARASET